Original paperSafety and efficacy assessment of carotid artery stenting in a high-risk population in a single-centre registry - Kosowski, Michał; Zimoch, Wojciech; Gwizdek, Tomasz; Konieczny, Radosław; Kübler, Piotr; Telichowski, Artur; Jankowska, Ewa A.; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Ischaemic stroke is the primary cause of long-term disability and the third most common cause of death. Internal carotid artery stenosis is an important risk factor for stroke and transient ischaemic attack (TIA). European Society of Cardiology (ESC) and American Heart Association (AHA) guidelines allow carotid artery stenting (CAS) as an alternative to endarterectomy in centres with low rates of death or stroke. Aim: To assess the safety and efficacy of CAS in a single-centre observation. Material and methods : We performed a retrospective analysis of all patients treated with CAS between March 2008 and July 2012. Clinical data and outcomes in both asymptomatic and symptomatic patients were analysed. Results : A total of 214 consecutive patients were included in the registry. Symptomatic patients accounted for 57% of the study group and were more likely to have a history of stroke and/or TIA that occurred more than 6 months before the procedure (50% vs. 8%, p < 0.001). Asymptomatic patients were more likely to have a history of coronary artery disease (88% vs. 61%, p < 0.001), and the rates of previous acute coronary syndrome and revascularisation were also higher in this group (58% vs. 41% and 71% vs. 52%, respectively, both p < 0.05). The symptomatic group had higher incidence of stroke in periprocedural and 30-day observation (4% vs. 0%, p < 0.05). There was no difference in incidence of adverse events in long-term observation. Conclusions : Carotid artery stenting is a safe and efficacious procedure. Every centre performing CAS should monitor the rate of periprocedural complications.